Nursing Knowledge and Skills in Hidradenitis Suppurativa: A Multi-Centre Exploratory Study - Lucía Vilanova-Trillo; Alba-Elena Martínez-Santos; Josefa-del-Carmen Fernández-De-La-Iglesia; Laura Salgado-Boquete; Ángeles Flórez (Nursing Reports)
Background/Objectives: Hidradenitis suppurativa (HS) is an under-treated chronic inflammatory disease that affects approximately 0.40–2% of the population. Despite the competences nurses have in wound care, little is known about their management of HS lesions. The objectives of this study were to determine the knowledge and skills of primary care nurses regarding HS as well as to analyse the aspects in which these nurses need to strengthen their competences. Methods: A multicentre exploratory cross-sectional study was carried out in all seven healthcare areas of the Galician Health Service (N-W Spain) during 2021–2022. A questionnaire was developed for the project and subsequently piloted; from it, four dimensions were established. Additionally, sociodemographic data were collected. A total of 211 primary care nurses participated. Results: Both total and dimension scores were lower than 5 out of 10 points. The participants showed more knowledge in the Diagnosis and Clinical Course dimension (M = 4.59 out of 10). An older age correlated with greater knowledge regarding Diagnosis and Clinical Course (rho = 0.196; p = 0.006). Conclusions: These findings highlight the importance of developing evidence-based continuous training in the management and detection of the disease, while reducing the consequences of HS on patients’ quality of life.